COT: an efficient and accurate method for detecting marker genes among many subtypes - Lu, Yingzhou; Wu, Chiung-Ting; Parker, Sarah J; Cheng, Zuolin; Saylor, Georgia; Van Eyk, Jennifer E; Yu, Guoqiang; Clarke, Robert; Herrington, David M; Wang, Yue (Bioinformatics advances, 2022)
Motivation Ideally, a molecularly distinct subtype would be composed of molecular features that are expressed uniquely in the subtype of interest but in no others—so-called marker genes (MGs). MG plays a critical role in the characterization, classification or deconvolution of tissue or cell subtypes. We and others have recognized that the test statistics used by most methods do not exactly satisfy the MG definition and often identify inaccurate MG. Results We report an efficient and accurate data-driven method, formulated as a Cosine-based One-sample Test (COT) in scatter space, to detect MG among many subtypes using subtype expression profiles. Fundamentally different from existing approaches, the test statistic in COT precisely matches the mathematical definition of an ideal MG. We demonstrate the performance and utility of COT on both simulated and real gene expression and proteomics data. The open source Python/R tool will allow biologists to efficiently detect MG and perform a more comprehensive and unbiased molecular characterization of tissue or cell subtypes in many biomedical contexts. Nevertheless, COT complements not replaces existing methods. Availability and implementation The Python COT software with a detailed user’s manual and a vignette are freely available at https://github.com/MintaYLu/COT. Supplementary information Supplementary data are available at Bioinformatics Advances online.